In-patient step count predicts re-hospitalization after cardiac surgery - Takahashi, T.; Kumamaru, M.; Jenkins, Sue; Saitoh, M.; Morisawa, T.; Matsuda, H. (2015)
Background Clinical significance of in-patient step count after cardiac surgery remains unknown. The aim of this study was to determine whether the number of steps walked during the in-patient stay after cardiac surgery predicts the risk of cardiac re-hospitalization in the following year. Methods One hundred and thirty-three patients who underwent cardiac surgery were included in this study. The number of steps was assessed using a triaxial accelerometer. One year after surgery, patients completed a postal survey to determine their health condition and occurrence of cardiac re-hospitalization. Results The mean number of steps walked during the last three in-patient days was 2460 ± 1549 (mean ± standard deviation). Of the 133 patients, there were 16 cases (12.0%) of cardiac re-hospitalization during the 1-year follow-up period. The average step count before discharge was significantly lower in the 16 patients who were re-hospitalized for cardiac causes (1297 ± 1232 versus 2620 ± 1524, p < 0.01). The cut-off value that predicted the occurrence of cardiac re-hospitalization on the receiver operating curve was 1308 steps (area under the curve: 0.783, p < 0.001, sensitivity: 0.814, specificity: 0.733). Cox proportional hazards analysis revealed that the strongest predictor of cardiac re-hospitalization was a low step count prior to discharge (=1308 steps, hazard ratio: 7.58; 95% confidence interval: 2.04–28.22). Conclusions In-patient step count appears to be a risk factor for cardiac re-hospitalization within the first year following cardiac surgery. Further studies are needed to clarify the clinical significance of step count both preoperatively and following discharge.